Sexual dysfunction among married multiple sclerosis patients in Kingdom of Saudi Arabia 2020 - Alqahtani, Zina Ali; Mushari, Bayan Yahya; Alsulayyim, Rahaf Saeed; Al-Qahtani, Nouf Mohammed; Alzailaie, Ameerah Khaled; Al-Hasher, Sara Khalid; Abumsmar, Lamya Ali; Gohman, Raghad Salem; Yahya, Dhay Mohammed; Almozher, Hajar Alhussain; Al-Hayaza, Shahad Hassan (International Journal Of Community Medicine And Public Health, 2020)
Background: Multiple sclerosis (MS) is a chronic inflammatory demyelinating disorder of the central nervous system characterized by episodic and progressive neurologic dysfunction resulting from inflammatory and autoimmune reactions. Sexual dysfunction (SD) is a common disorder in both male and female patients complaining of multiple sclerosis (MS). Methods: A descriptive cross-sectional study was conducted including patients with MS attending Arfa MS Society in Saudi Arabia. Data were collected from participants using electronic pre-structured questionnaire. The questionnaire was uploaded online using social media platforms. Multiple sclerosis intimacy and sexuality questionnaire (MSISQ-19) was used to assess sexual dysfunction. Patient health questionnaire (PHQ-9) was used to assess patient’s psychological health and depression. Results: The study included 303 patients with multiple sclerosis whose ages ranged from 20 to 62 years old with mean age of 34.7±8.2 years old. About 75.6% took a long time to reach orgasm. Feeling sexual pleasure was reported by 73.3% of the patients and 70% reported that they had less interest or less desire for sexual activity. In general, the patients score regarding primary sexual dysfunction was 13.7 out of 25 (54.8%), 24.4 out of 45 for secondary sexual dysfunction (45.2%), and 12.6% out of 25 for tertiary sexual dysfunction (50.3%). Conclusions: In conclusion, the study revealed that sexual dysfunction in multiple sclerosis patients is not a simple process. MS was associated with high sexual dysfunction with other psychological disorders affecting male and female patients equally regardless age and educational level.